Surgical technique and complications of enucleation - Obuchowska, Iwona; Mariak, Zofia; Elmdhm, Sulyman (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Enucleation consists of removal of the entire globe and portion of the optic nerve from the orbit. This surgical procedure is generally accepted treatment for intraocular malignancies, a blind painful eye, severely traumatized eye, phthisis bulbi and improvement of cosmetic look. In this review, the authors discuss the current surgical technique of enucleation with orbital implant placement and their complications.